Cardiovascular sequelae of dengue fever: a systematic review. (3rd June 2022) - Rahim, Abdur; Hameed, Ali; Ishaq, Uzma; Malik, Jahanzeb; Zaidi, Syed Muhammad Jawad; Khurshid, Hajra; Malik, Asmara; Satti, Danish Iltaf; Naz, Hifza
ABSTRACT: Introduction: Dengue is one of the most important viral diseases globally and a majority of symptomatic infections result in a benign course. However, a small number of patients develop severe manifestations, including the cardiovascular (CV) manifestations, including myocardial impairment, arrhythmias, and fulminant myocarditis. Areas covered: Electronic databases, including PubMed/MEDLINE, EMBASE, Scopus, and CINAHL were searched for articles incorporating CV manifestations of dengue fever (DF). Expert opinion: Included studies involved 6, 773 patients, and 3, 122 (46.1%) exhibited at least one cardiac manifestation. Electrocardiogram (ECG) abnormalities (30.6%) included sinus bradycardia (8.8%), nonspecific ST-T changes (8.6%), ST depression (7.9%), and T-wave inversion (2.3%). Mechanical sequelae were present in 10.4%, including left ventricular (LV) systolic dysfunction (5.7%), and myocarditis (2.9%). Pericardial involvement was noted as pericarditis (0.1%), pericardial effusion (1.3%), and pericardial tamponade (0.1%). Apart from that, the cardiac injury was depicted through a rise in cardiac enzymes (4.5%). The spectrum of CV manifestations in dengue is broad, ranging from subtle ST-T changes to fulminant myocarditis and the use of contemporary techniques in diagnosing cardiac involvement should be employed for rapid diagnosis and treatment.